On the pricing of quality attributes at movie theaters. Issue 1 (3rd April 2019) - Arteaga, Julio C.; Coronado, Daniela; Flores, Daniel
ABSTRACT: In this study, we use hedonic and conjoint analyses to estimate the effects of a series of service attributes such as VIP (top luxury), IMAX, X4D (a 3D movie projection with synchronized physical effects), JUNIOR (an auditorium with a playground for kids), and 3D on admission prices at movie theaters. As far as we know, this is the first effort to measure consumers' willingness to pay for a set of quality service attributes in this industry using these methods. Our estimates can serve as a guide for pricing decisions at movie theaters. Moreover, they can be used to assess investments. Some of the quality attributes that we study have large implicit prices. Nevertheless, they can be very costly or may substantially reduce the seating capacity of theaters. Therefore, we provide an example illustrating how managers and investors can use our willingness to pay estimates to evaluate investing in each of these features.